The Relationship between Family Tie and Marital Stability in Ohafia Local Government Area - Nneoma Precious, Jolly-James (Researchparks Publishing, 2023)
In Ohafia Local Government Area, the dynamic interplay between family ties and marital stability presents a complex problem. This region, characterized by its strong cultural and familial bonds, raises questions about how these deep-rooted family connections impact the resilience and longevity of marriages. The intricate relationships within families in Ohafia, including extended family influence, cultural expectations, and traditional values, potentially exert significant effects on marital harmony and stability. Understanding these relationships is crucial for addressing marital challenges and enhancing family wellbeing in the community. The aim of the study is to explore the relationship between family ties and marital stability in Ohafia Local Government Area and its implications. This study utilizes Family Systems Theory to examine the influence of familial relationships on marital stability. A correlational research design was employed, with a sample size of 400 determined by Taro Yamene’s formula and selected through random sampling across towns and villages in Ohafia. Data analysis involved Pearson Product Moment Correlation Coefficient using SPSS version 25. The study found a significant correlation between family ties and marital stability, underscoring the influence of familial relationships on marital outcomes. The results affirm Family Systems Theory, suggesting that family dynamics, including extended family involvement, deeply affect marital satisfaction and longevity in Ohafia. It is recommended to implement family-oriented educational programs and counseling services that focus on enhancing understanding and management of familial influences on marriages. Further research should explore intervention strategies that can strengthen marital bonds within the context of family dynamics in Ohafia.